The Risk Factor of Hypertension in Bali: Data Study of Indonesia Basic Health Survey 2018 - I Nyoman Purnawan; Nyoman Suarjana (PT.Mantaya Idea Batara, 2026)
Background: The prevalence of hypertension among individuals aged 15 years and older in Bali has increased in recent years. Objective: This study analyzed risk factors for hypertension in Bali using data from the 2018 Indonesian Basic Health Survey Methods: A quantitative, cross-sectional design was employed, utilizing secondary data from the 2018 survey. The sample included 14,494 respondents aged 15 years and above in Bali Province, of whom 2,290 had hypertension. Data were analyzed using univariate and bivariate methods, including chi-square tests, with Odds Ratios (OR) and 95% Confidence Intervals (CI) calculated Results: The prevalence of hypertension was found to be 18%. Comorbidities significantly associated with hypertension included stroke (OR=8.44), cardiovascular disease (OR=2.49), arthritis (OR=2.28), and cancer (OR=1.64). Sociodemographic factors such as low education level and marital status were also associated with hypertension. Behavioral factors included low physical activity, alcohol consumption, obesity, and overweight status. Obesity emerged as a dominant risk factor (OR = 3.38). Conclusion: The findings indicate that hypertension in Bali is influenced by comorbidities, sociodemographic characteristics, behavioral factors, and body mass index. Prevention and control strategies should focus on health promotion, early detection, and the adoption of healthy lifestyle modifications.